Dialogue on Ethiopian Agricultural Development: Report of a conference, Addis Ababa, Ethiopia, 12 November 2009 - International Livestock Research Institute (International Livestock Research Institute, 2011)
The dialogue on Ethiopian Agricultural Development was organized by the Ministry of Agriculture and Rural Development (MoARD) of the Federal Democratic Republic of Ethiopia and the International Livestock Research Institute (ILRI) to honour Professor Gebisa Ejeta, winner of the 2009 World Food Prize. The dialogue was held on 12 November 2009 at the United Nations Conference Centre. It was opened by H.E. Ato Girma Woldegiorgis, President of the Federal Democratic Republic of Ethiopia. Professor Gebisa received the prestigious prize on 15 October at Iowa’s state capital, Des Moines, USA. His research with sorghum hybrids resistant to drought and the devastating Striga weed have dramatically increased the production and availability of one of the world’s five principal grains and enhanced the food supply of hundreds of millions of people in sub- Saharan Africa. Professor Gebisa’s high academic standing in his undergraduate years paved the way to financial assistance and entrance into higher education institutions, leading to his bachelor’s degree in plant science in 1973 from the Alemaya College of Agriculture. It was in 1973 that his mentor Dr Berhane Gebre-Kidan introduced Gebisa to a renowned sorghum researcher, Dr John Axtell of Purdue University, who invited him to assist in collecting sorghum species from around Ethiopia. Dr Axtell was so impressed with Gebisa that he invited him to become his graduate student at Purdue University. Gebisa entered Purdue University in 1974, earning his PhD in plant breeding and genetics. He later became a faculty member at Purdue, where today he holds a distinguished professorship. It is Professor Gebisa’s dedication to helping poor farmers feed themselves and their families and rise out of poverty that propelled his life’s work. Professor Gebisa Ejeta spoke on science-based agricultural development with particular emphasis on Ethiopia. H.E. Dr Abera Deressa, State Minister of MoARD; Dr Solomon Assefa, Director General of the Ethiopian Institute of Agricultural Research; and Professor Belay Kassa, President of Haramaya University made presentations on the challenges, opportunities and achievements of agricultural research in Ethiopia and the role of agricultural universities. This was followed by a panel discussion in which valuable remarks were made by personalities from different renowned institutions and universities.